Updates on BES1/BZR1 Regulatory Networks Coordinating Plant Growth and Stress Responses - Kono, Alfredo; Yin, Yanhai (Frontiers in Plant Science, 2020)
Brassinosteroids (BRs) play pivotal roles in the regulation of many dimensions of a plant’s life. Hence, through extensive efforts from many research groups, BR signaling has emerged as one of the best-characterized plant signaling pathways. The key molecular players of BR signaling from the cell surface to the nucleus that important for the regulation of plant growth and development are well established. Recent data show that BRs also modulate plant responses to environmental stresses such as drought and pathogen infection. In this mini review, we present recent progress on BR signaling specifically on the post-translational SUMO modification of BR’s master regulators, BES1/BZR1. We also discuss recent findings on the crosstalk between BR and Jasmonates signaling pathways to balance growth during pathogen infections. Finally, we describe the current update on the molecular link between BR signaling and intracellular auxin transport that essential for plant development.